Co-habiting with Ghosts Knowledge, Experience, Belief and the Domestic Uncanny. - Lipman, Caron (Farnham : Ashgate Publishing Ltd, 2014)
This book sets out to explore the questions posed by the reality of living in a 'haunted home' and attends to the ways in which households in England and Wales understand their experience of haunting in relation to ideas of subjectivity, gender, materiality, memory, knowledge and belief. It explores home as a place both dynamic and differentiated, illuminating the complexity of 'everyday' experience - the familiarity of the strange as well as the strangeness of the familiar - and the ways in which home continues to be configured as a distinctive space.
Cover; Contents; Acknowledgements; 1 Approaching the Ghost; Part I: Spaces and Times of the Haunted Home; 2 The Material Uncanny; 3 The Temporalities of the Haunted Home; Part II: Strategies of Cohabitation; 4 Embodying, Domesticating, Gendering the Ghost; 5 Strategies of Distance and Communication; Part III: Belief, Knowledge and Experience; 6 Knowledge and Uncertainty; 7 Belief, Evidence and Experience; Conclusion: The Liminal Home/Self; Appendix: The Households; References; Index
Description based upon print version of record.
Keywords: Haunted houses -- England; Haunted houses -- Wales; Ghosts -- England; Ghosts -- Wales; BODY, MIND & SPIRIT / Parapsychology / General; Electronic books